2013
DOI: 10.1038/bjc.2013.571
|View full text |Cite
|
Sign up to set email alerts
|

Response of high-risk of recurrence/progression bladder tumours expressing sialyl-Tn and sialyl-6-T to BCG immunotherapy

Abstract: Background:High risk of recurrence/progression bladder tumours is treated with Bacillus Calmette-Guérin (BCG) immunotherapy after complete resection of the tumour. Approximately 75% of these tumours express the uncommon carbohydrate antigen sialyl-Tn (Tn), a surrogate biomarker of tumour aggressiveness. Such changes in the glycosylation of cell-surface proteins influence tumour microenvironment and immune responses that may modulate treatment outcome and the course of disease. The aim of this work is to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 28 publications
4
37
0
Order By: Relevance
“…The S6T was further evaluated in FFPE healthy urothelium from six necropsied male individuals, which confirmed its cancer‐associated nature. Recently, we have described that the presence of S6T and STn in bladder tumours was associated with a better response to BCG immunotherapy for more aggressive NMIBC, suggesting that O ‐6 sialylation plays a key role in bacillus binding to the epithelium (Lima et al ., ). Such observations reinforce the importance of including alterations in glycosylation in panomics predictive molecular models.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The S6T was further evaluated in FFPE healthy urothelium from six necropsied male individuals, which confirmed its cancer‐associated nature. Recently, we have described that the presence of S6T and STn in bladder tumours was associated with a better response to BCG immunotherapy for more aggressive NMIBC, suggesting that O ‐6 sialylation plays a key role in bacillus binding to the epithelium (Lima et al ., ). Such observations reinforce the importance of including alterations in glycosylation in panomics predictive molecular models.…”
Section: Resultsmentioning
confidence: 97%
“…Interestingly, this mimics the sialylation of the Tn antigen, whose biological and clinical significance has been extensively studied by our group. Furthermore, we have again reinforced the association between STn antigen expression and aggressive disease, raising to over 300 the number of evaluated tumour sections of different clinicopathological classifications and aetiologies (Bernardo et al ., ; Cabral et al ., ; Costa et al ., ; Ferreira et al ., ; Lima et al ., ; Peixoto et al ., ; Santos et al ., ). Significant efforts should be put on providing accurate quantification of these antigens using high‐throughput glycomics approaches and on developing highly specific ligands.…”
Section: Resultsmentioning
confidence: 97%
“…In addition, efforts should continue to be devoted towards a more comprehensive and integrated understanding of bladder cancer pathways, the tumor microenvironment and cancer-associated immune responses and their influence in treatment response. Namely, future it would be important to ponder possible factors modulating targetmolecules expression and response profile to immunotherapy, such as the highly variable mutational spectrum of bladder cancers [19,180] and inter-patients variability, as translated by our most recent works in the field of pharmacogenetics [181][182][183]. The tumor microenvironment, in particular the immune responses occurring in stroma [184], is another critical aspect that as remained mostly disregarded and warrants careful investigation in the future.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…In addition, our group has recently highlighted that advanced stage bladder cancer cells present profound alterations in the glycosylation of cell-surface proteins, which are key mediators in disease progression and dissemination [185][186][187]. Furthermore, we have demonstrated that altered protein glycosylation may directly influence the response to immunotherapy by modulating cancer cell recognition [182] and dendritic cells function, limiting their capacity to trigger protective anti-tumor T cell responses [188]. Glycoproteomic studies are ongoing to identify unique cancer-associated glycoprotein subsets envisaging highly specific cancer biomarkers, the development of novel therapeutic antibodies and strategies to overcome tumor-induced immune tolerogenic mechanisms.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Of these patients, 15% develop tumor progression and form distant metastases. [2] Despite many efforts, [3][4][5] there are currently no biomarkers that can predict patient's prognosis and that discriminate those who will respond to BCG treatment from those who would be best served by more aggressive therapy such as cystectomy or, alternatively, radio-and chemotherapy. BCG instillations can cause side effects ranging from incommodious cystitis to sepsis and even death of patients in rare cases.…”
Section: Introductionmentioning
confidence: 99%